Efficacy of lung cancer screening at the American University of Beirut Medical Center - Harb, Tarek; Alhafi, Anas; Tfayli, Arafat H. (Frontiers in Oncology, 2023)
In Lebanon, a dedicated screening program for lung cancer is absent. Screening is largely based on the recommendation of an informed physician or the initiative of a patient. To better understand the situation, it is important to look at the available data on patients currently being screened for lung cancer in this country. Our aim in this study is to review the data and compare it to that in the literature, as well as to assess the efficacy of the screening process followed.Methods: Our study accessed the electronic medical records of patients at AUBMC, a tertiary care center in Lebanon. We collected information on patients who underwent screening low-dose computed tomography (LDCT) scan between June 2019 and June 2021 inclusive. Records of all patients who underwent a non-contrast computed tomography (CT) scan at AUBMC during this period were collected and analyzed.Results: On average, our population had a 52.6 pack-year smoking history. 47% of our population had an accurate pack-year reported while 12% did not have enough information to even estimate their packyear history. When looking at the accurate and estimated data, 5% of our population did not even meet the ≥20 pack-year smoking history. 8 patients had positive findings on the screening LDCT, which we defined as suspicious findings that require further workup (e.g. PET/CT or biopsy) or other significant incidental findings.A well-organized program for lung cancer screening in Lebanon is absent. Screening largely depends on the initiative of the physician or the patient. We were able to uncover multiple flaws in the screening method used, including poor documentation and follow up. Although the screening method adopted retained some benefits in terms of detecting early malignancy, it lacks proper organization and was not ideal. A better, systematized screening program is needed to have optimal outcomes.